Educating children and young people with fetal alcohol spectrum disorders : constructing personalised pathways to learning - Blackburn, Carolyn, 1963-; Carpenter, Barry; Egerton, Jo. (Oxon [England] : Routledge, 2012)
"The range of learning difficulties associated with children who have Fetal Alcohol Spectrum Disorders (FASD) has been highlighted as an emerging but little understood area of Special Educational Needs. This engaging, timely and highly practical book will raise awareness about FASD and its associated difficulties across the entire education workforce. It provides a range of specialist, tried-and-tested practical teaching and learning strategies from which teachers and support staff may construct personalised learning plans for students with FASD, and will help improve outcomes for all their children. It also: - Explains the links to neuroscience that can lead to a child having FASD. - Discusses the overlapping and co-existing disorders, such as ADHD and autism spectrum disorders. - Shows how to support and empower teachers. - Provides ready to use teaching resources and strategies that can be used directly in the classroom. Informed by the very lastest research and written by leading experts in the field, Educating Children with Fetal Alcohol Spectrum Disorders will prove invaluable for Initial Teacher Training students as well as being of interest for Newly Qualified and experienced teachers who are engaging in Continuing Professional Development"-- Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Learning disabled children -- Education; Fetal alcohol syndrome; Individualized instruction; Neurosciences; Electronic books